Republic of Tunisia : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Tunisia. The analysis of practices is based among others on the review of a sample of 16 financial statements prepared in accordance with Tunisian accounting standards, including 6 listed enterprise sector companies, 3 listed credit institutions and 3 insurance undertakings (of which 2 are listed). The assessment uses International Financial Reporting Standards (IFRS), International Standards on Auditing (ISA), and the relevant portions of European Union (EU) law (also known as the acquis communautaire) as benchmarks and draws on international experience and good practices in the field of accounting and audit regulation. As Tunisia deepens its partnership with the EU and becomes more integrated in the world market, the country monitors the development of the acquis communautaire and enacts legislation that draws upon it. This report recommends changes to law and regulations to align the statutory framework with evolving internationally accepted practices. As the new regulations come into force, priorities will then turn toward building the monitoring, supervisory, and disciplinary regimes necessary to ensure effective compliance.